MANAGEMENT OF WEBSITE-BASED VILLAGE INFORMATION SYSTEM BY VILLAGE GOVERNMENT PARTNERS IN PANGANDARAN VILLAGE PANGANDARAN DISTRICT PANGANDARAN REGENCY: Array - Ega Megawati; Kiki Endah (Faculty of Social And Political Science Universitas Galuh, 2021)
This research is based on the problem that the management of village information system based on website by village government partners in Pangandaran village pangandaran subdistrict is still not optimal, this happens because of the lack of initial leveling, lack of availability of monitoring tools, lack of socialization by Village Government Partners, and lack of Human Resources who carry out tasks on the management of Village Information Systems. Therefore, this study aims to find out how the Management of Village Information System based on website by Village Government Partners in Pangandaran Village Pangandaran District Pangandaran Regency. The research method used in this research is qualitative descriptive by conducting observations and interviews to 9 (Nine) informants, namely 2 (two) Village Assistants as operators and field technicians, Village Heads, Village Secretaries, Service Kasi Staff, Planning Kaur, Village Consultative Agency, 2 (two) Community Leaders, namely the Village Head. The results of this study showed that the management of village information system based on the website by the Village Government Partners in Pangandaran Village Pangandaran District Pangandaran Regency as a whole from various activities carried out has been running well but still not optimal. It can be known from the information transformation in terms of data collection and information is still lacking, from information communication in terms of socialization implementation, briefing, implementation instructions are also lacking, as well as from control in terms of coaching is still lacking. But for the rest has been implemented well, especially in the formulation and identification of activities that have been carried out through the form of cooperation supported by the provision and use of adequate infrastructure.